Effectiveness and Safety of Early High-Efficacy Versus Escalation Therapy in Relapsing-Remitting Multiple Sclerosis in Argentina. Issue 3 (14th May 2022) - Rojas, Juan Ignacio; Patrucco, Liliana; Alonso, Ricardo; Garcea, Orlando; Deri, Norma; Carnero Contentti, Edgar; Lopez, Pablo A.; Pettinicchi, Juan Pablo; Caride, Alejandro; Cristiano, Edgardo
Abstract : Objective: Escalation (ES) and early high-efficacy (EHE) therapies have been the main treatment strategies adopted in multiple sclerosis (MS) in recent years. The aim of this study was to compare the effectiveness and safety of EHE versus ES strategies in MS patients from Argentina. Methods: This is a retrospective multicenter cohort study in Argentina. Eligible patients were categorized into 2 groups as follows: EHE if received natalizumab, ocrelizumab, rituximab, alemtuzumab, mitoxantrone, or cladribine; and ES if received interferon β, glatiramer acetate, teriflunomide, dimethyl fumarate, or fingolimod as initial therapy. The primary outcome was confirmed disability progression (Expanded Disability Status Scale [EDSS] increase). Additional outcomes included the proportion of patients and time to: EDSS 6; new relapses; new T2–magnetic resonance imaging (MRI) lesions; no evidence of disease activity; and specific adverse events. Propensity score–based nearest-neighbor matching (without replacement) was applied to homogenize the sample, and Cox regression model stratified by matched pairs was used for the analysis. Results: After propensity score matching, 193 and 112 patients were retained in the ES and EHE groups, respectively. The EHE significantly decreased the risk of EDSS progression (hazard ratio [HR], 0.62; 95% confidence interval [95% CI], 0.40–0.98; P = 0.04), relapses (HR, 0.66; 95% CI, 0.49–0.89; P = 0.006), and new MRI activity during follow-up (HR, 0.55; 95% CI, 0.40–0.75; P < 0.001). No significant differences were observed in specific adverse events between groups. Conclusions: Our study shows that EHE therapies prevent disease progression, relapses, and new MRI lesions and demonstrated no increased risk of specific adverse events when compared with ES therapy. These data should be considered when selecting a specific treatment for MS patients.